(untitled) (REMUNOM, 2024)
The need for a good diet gives rise to sustainable alternatives that can meet the lack of food. Urban agriculture is being pointed out as an alternative that fits perfectly in this scenario and is considered a sustainable practice, usually organic, which occupies several spaces, such as backyards of houses, common areas in small and large cities, which provides the production of vegetables, fruit crops, ornamental plants and even livestock in a sustainable way. This article aimed to elucidate how urban agriculture is transforming urban spaces. In addition to examining potential impacts, at the same time clarifying its growing role in building sustainable and livable cities. The methodology was through a survey of articles published in scientific journals, renowned websites, books and magazines. As a search strategy were used the keywords (urban agriculture, urban gardens, vertical garden, agriculture in small spaces and sustainable agriculture) as guidelines and the search was conducted online. After the survey, 622 related documents were found, which subsequently adopted the criterion of selecting more current documents (2021-2022), leaving 20 that were used in this article, related in the references. The results show that urban agriculture is consolidating as a transformative force, shaping urban spaces in a way that transcends simple food production, paving the way for a more holistic and sustainable approach to urban development, providing both environmental and social benefits and promoting food security to those involved and other communities. It also takes advantage of underused and often abandoned spaces. Keywords: Urban agriculture, urban vegetable gardens, vertical vegetable garden, agriculture in small spaces and sustainable agriculture.